The administration of Muslim affairs in the Straits Settlements during the 19th century - Mansor Majdin, Mohamad Firdaus (IIUM Journal of Religion and Civilisational Studies (IJECS), 2018)
The year 1786 marked the beginning of the British official administration in Malaya through the effective manoeuvre of the East India Company (E.I.C.), particularly in Francis Light’s view of the island’s geographically and economically strategic positions to the British Empire. As the British started to step into the island, they brought in various aspects of British customs and cultures which manifested in the areas of administration or governance (formation of the Straits Settlements included Singapore and Malacca in 1826), education, social order, justice, et cetera. The British had, specifically, introduced English Law in the island as the sole-governing law which regulated the inhabitants’ lives. In this regard, demographically speaking, the Muslim community formed a substantial number of the population in the colony. Thus, as far as Islam is concerned, the Muslim community is governed by Islamic Law (Shari’ah) and the customary laws (adat) in their daily lives. The Islamic Law is synonymous with the Mohammedan Law which was introduced in the colony in 1888 by the British colonial government.